EFFECT OF GENETIC AND SOME OTHER SOURCES OF VARIATION ON DRY PERIOD IN MALVI COWS - Sharma, Harish; Tomar, SS; Kumar, Amit (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The data for the present investigation pertained to 1647 observations of dry period (DP) on 409 Malvi cows maintained at Govt. Cattle Breeding Farm, Agar, Shajapur (M.P.), covering a period of 48 years from 1962 to 2009. The least squares analysis of variance revealed mean dry period in these cows to be 130.78±9.10 days and was significantly affected by period (P< 0.01), season (P< 0.01), parity (P< 0.01) and inbreeding (P< 0.05) while effect of sire was non-significant. The mean dry period for inbred animals was significantly higher than that of non-inbred. Heritability estimates for DP was obtained as 0.09±0.11. It was therefore concluded, that inbreeding had deteriorating effect on the dry period and hence to improve this trait in the herd, avoidance of inbreeding along with ameliorative managerial practices should be undertaken.